Jaceosidin inhibits proliferation of human bladder cancer T24 cells through induction of cell cycle arrest and apoptosis (Bangladesh Journal of Pharmacology, 2013)
Jaceosidin, isolated from Artemesia argyi, has been shown to possess promising anticancer potential against various cancer cells. However, its effect against bladder cancer cells remained unknown. In this study, for the first time, we investigated the effects of jaceosidin on cell proliferation, cell cycle, and apoptosis in bladder cancer T24 cells by using MTT assay and flow cytometric analysis. The results revealed that jaceosidin decreased the cell viability of bladder cancer T24 cells in a dose- and time-dependent manner. Flow cytometric analysis demonstrated that jaceosidin significantly triggered apoptosis in T24 cells and arrested cell cycle at G2/M phase in a time-dependent manner. Further characterization showed that jaceosidin-induced apoptosis is associated with dissipation in mitochondrial membrane potential (??m), up-regulation of Bax and down-regulation of Bcl-2 in jaceosidin-treated T24 cells. These in vitro results suggested that jaceosidin should be further examined for in vivo activity and molecular mechanism in human bladder cancer.